Combination anti‐obesity medications to effectively treat bariatric surgery weight regain at an academic obesity center - Gunther Wong; Erica M. Garner; Sahar Takkouche; Matthew D. Spann; Wayne J. English; Vance L. Albaugh; Gitanjali Srivastava (Obesity Science & Practice, 2023)
Abstract Background Combination anti‐obesity medications (AOMs) to treat postoperative bariatric surgery weight regain have limited data on their use in the clinical setting. Understanding the optimal treatment protocol in this cohort will maximize weight loss outcomes. Methods A retrospective review of bariatric surgery patients (N = 44) presenting with weight regain at a single academic multidisciplinary obesity center who were prescribed AOM(s) plus intensive lifestyle modification for 12 months. Results Age: 28–76 years old, 93% female, mean weight 110.2 ± 20.3 kg, BMI 39.7 ± 7.4 kg/m2, presenting 5.2 ± 1.6 years post‐bariatric surgery [27 (61.4%), 14 (31.8%), and 3 (6.8%) laparoscopic Roux‐en‐Y gastric bypass (RYGB), laparoscopic vertical sleeve gastrectomy (VSG), and open RYGB, respectively], with 15.1 ± 11.1 kg mean weight gain from nadir. Mean weight loss after medical intervention at 3‐, 6‐, and 12‐month time points was 4.4 ± 4.6 kg, 7.3 ± 7.0 kg, and 10.7 ± 9.2 kg, respectively. At 12 months, individuals prescribed 3 or more AOMs lost more weight than those prescribed one (−14.5 ± 9.0 kg vs. −4.9 ± 5.7 kg, p < 0.05) irrespective of age, gender, number of comorbidities, initial weight or BMI, type of surgery, or GLP1 use. RYGB patients lost less weight overall (7.4% vs. 14.8% VSG respectively; p < 0.05). Conclusions Combination AOMs may be needed to achieve optimal weight loss results to treat post‐operative weight regain.